Hypervirulent Klebsiella pneumoniae have better clinical outcomes than classical Klebsiella pneumoniae for lower respiratory tract infection patients - Xianxia Zhuo; Zichen Lei; Danni Pu; Yongli Wu; Jiankang Zhao; Bin Cao (BMC Microbiology)
Abstract Background The clinical outcomes and microbiological features of lower respiratory tract infections (LRTIs) caused by hypervirulent Klebsiella pneumoniae (hvKp) and classical Klebsiella pneumoniae (cKp) have not been well understood. Methods This study collected 287 non-repetitive Klebsiella pneumoniae isolates from 287 LRTI patients. All these strains underwent annotation for resistance and virulence factors, with 141 strains undergoing mouse infection experiments to assess their virulence. The primary clinical outcomes of these patients were evaluated, including intensive care unit (ICU) admission and in-hospital mortality rates. Results A total of 46 capsule serotypes were identified. Among these isolates subjected to mouse infection experiments, the proportions of strains exhibiting hypervirulent phenotypes were 92.6% (25/27), 92.1% (35/38), 80% (4/5), 25% (1/4), 10.5% (2/19), and 7.1% (1/14) for K2, K1, K20, K54, K47, and K25, respectively. Therefore, K1, K2, and K20 K. pneumoniae were defined as hvKp. In addition, the rates of ICU admission and in-hospital mortality for hvKp-infected patients were significantly lower than those of cKp-infected patients (51.4% vs. 65.9%, χ2 = 4.722, p = 0.03 and 8.6% vs. 29%, χ2 = 12.133, p < 0.001). Notably, among the cKp group, the cKp-ST11 subgroup had higher rates of ICU admission (77% vs. 58.5%, χ2 = 7.981, p = 0.005) and in-hospital mortality (44.8% vs. 18.5%, χ2 = 17.585, p < 0.001) than cKp-nonST11 subgroup. Conclusions These findings suggest that capsule serotype is a more accurate factor for the prediction of the virulence phenotype, while hvKp have better clinical outcomes than cKp for LRTI patients. Furthermore, the cKp-ST11 subgroup has the worst prognosis than cKp-nonST11 subgroup.